2019
DOI: 10.1186/s12870-019-2085-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen availability prevents oxidative effects of salinity on wheat growth and photosynthesis by up-regulating the antioxidants and osmolytes metabolism, and secondary metabolite accumulation

Abstract: BackgroundSalinity is one of the damaging abiotic stress factor. Proper management techniques have been proposed to considerably lower the intensity of salinity on crop growth and productivity. Therefore experiments were conducted to assess the role of improved nitrogen (N) supplementation on the growth and salinity stress tolerance in wheat by analyzing the antioxidants, osmolytes and secondary metabolites.ResultsSalinity (100 mM NaCl) stress imparted deleterious effects on the chlorophyll and carotenoid synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 71 publications
11
65
0
Order By: Relevance
“…Moreover, the higher reduction in the SS cultivar indicated a more severe adverse effect of salinity on the SS cultivar, which is consistent with previous reports [41,42]. Recent studies in tomato [17], wheat [21], Hordeum vulgare [43], Carrizo citrange [44], Spartina alterniflora [45], Sorghum bicolor [46], and Brassica [34] showed that higher nitrogen supplementation can regulate the salinity tolerance and improve plant growth. In the experiments reported here, application of 2.5 mmol·L −1 nitrogen increased the SL, NL per plant, and total biomass in both ST and SS genotypes under salt stress (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the higher reduction in the SS cultivar indicated a more severe adverse effect of salinity on the SS cultivar, which is consistent with previous reports [41,42]. Recent studies in tomato [17], wheat [21], Hordeum vulgare [43], Carrizo citrange [44], Spartina alterniflora [45], Sorghum bicolor [46], and Brassica [34] showed that higher nitrogen supplementation can regulate the salinity tolerance and improve plant growth. In the experiments reported here, application of 2.5 mmol·L −1 nitrogen increased the SL, NL per plant, and total biomass in both ST and SS genotypes under salt stress (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in support of the outcomes of the present study, several other scholars reported that co-application of nitrogen significantly boosted the level of antioxidant enzymes in soybean [56], Catharanthus roseus [57], and blueberry [58]. Nitrogen serves as a first line of defense against internal and environmental oxidative stressors [17,21,59,60]. Moreover, the positive effect of nitrogen may be related to nitrogen being an effective component of antioxidant enzymes and antioxidants [17,27].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Cadmium retards vital physio-biochemical activities in plants, which include photosynthesis, biosynthesis of chlorophyll and accessory pigments, and the uptake and assimilation of essential mineral nutrients by triggering the overproduction of reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), hydrogen peroxide (H 2 O 2 ), superoxide radical (O 2 • − ), and the hydroxyl radical (OH•) [5,6]. ROS accumulation causes high toxicity in plant cells [7][8][9][10][11][12][13][14][15][16]. Cadmium evokes peroxidation of membrane lipids and modulates the expression of genes of antioxidant defense systems in plants [17].…”
Section: Introductionmentioning
confidence: 99%